Hubungan Antara Transisi Pemasaran dari Pemasaran Tradisional ke Pemasaran Digital dengan Volume Penjualan (Studi Pada Usaha Mikro Kecil dan Menengah di Kota Tangerang) - Aqshal Virgiananda Salendar; Susilo Toto Raharjo (Faculty of Economics and Business | Universitas Diponegoro, 2022)
This study is intended to describe the effect of digital marketing on the increase in sales volume of MSMEs. The problems in this study include how much increase in sales volume after implementing digital marketing and the reasons why business owners do not implement digital marketing. The purpose of this study is to determine the effect of digital marketing on product sales volume, and to find out the factors that cause entrepreneurs not to implement digital marketing This research is a qualitative type of research with a phenomenological approach. Data collection is done by in-depth interview method. The resource persons in this study were the owners of Micro, Small and Medium Enterprises in Tangerang which opened 10 people. The findings in this study include three things: (1) The reason why business owners switch to digital marketing, namely the decline in business sales, (2) Does sales volume increases after implementing digital marketing, which is 80% to 200%, (3) The reason why owners the business does not or has not implemented digital marketing, which includes the incompatibility of business with the application of digital marketing; digital marketing is felt to be inefficient and complicated as well as competition with suppliersKeywords: marketing transition, digital marketing, sales volume, e-commerce